SISTEM MONITORING DAN EVALUASI KINERJA GURU BERBASIS WEB MONITORING SYSTEM AND TEACHER PERFORMANCE EVALUATION BASED ON WEB (Information Technology and Telematics, 2015)
ABSTRACT Technological developments are, in particular information technology develops very rapidly. Nowadays we often hear about Internet technology is the latest development of information technology is very rapid. Where the teacher is seen as a force profesional educators in charge of planning and implementing the learning process, assess learning outcomes, conduct guidance and training. Referring to the matter, formulation of the problem in this study is monitoring and evaluating the performance of teacher.Purpose of this study is on how teachers can be said both in terms of teaching high school Mardsiswa. The benefits of this research is expected to help a teacher can understand his profession as a school teacher method this time using the method of discussion where this method is used to discuss the teacher's performance in terms of teaching, this method is also supported by the system Macromedia Dreamweaver, PHP, Apache, MySQL and Photo shop. In the teacher's performance evaluation system of teachers can find out how well teachers perform their duties in teaching school to see the teacher's performance through the medium of the Internet, because the Internet allows teachers to know how well the performance of teachers for teaching in schools. Keywords: Macromedia Dreamweaver, PHP, Apache, MySQL and Photo shop